The effect of animal-assisted therapy on fine motor skill development. - McWatters, M. (The Young Researcher)
This study investigated the effect of weekly animal assisted activities utilizing guinea pigs on the fine motor development of children in grades kindergarten through third while also aiming to find more engaging and effective methods of occupational therapy for children in particular. An experimental research method was used to obtain quantitative data measuring fine motor ability through three different baseline data tests before and after a four week period. These baseline tests were implemented on both a control group and an experimental group. However, the experimental group had weekly interaction with guinea pigs between the two baseline data tests while the control group made no change to their daily routine. Ultimately, it was found through correlational research methods that animal assisted activities can be beneficial for fine motor development as the experimental group, on average, showed a much greater improvement in the tests over four weeks than the control group.